Synergistic Corrosion Inhibition Effect of Rice Husk Extract and KI for Mild Steel in H2SO4 Solution - Marta Pramudita; Sukirno Sukirno; Mohammad Nasikin (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The corrosion inhibition of rice husk extract for bio-corrosion in mild steel in 1 M of H2SO4 solution and the effect of adding potassium iodide were investigated using the weight-loss method with a variable solution temperature and various bio-inhibitor concentrations. The addition of potassium iodide can significantly increase the efficiency of rice husk extract. The highest efficiency is 95.89% at 1,250 ppm of inhibitor concentration at a temperature of 313 K. The inhibition efficiency of rice husk extract is synergistically increased with the addition of potassium iodide. The characteristics of the adsorption inhibitors were assessed using the Langmuir isotherm adsorption approach at all studied concentrations and temperatures. The synergy of rice husk extract and potassium iodide was examined using thermodynamic and kinetic parameters.